THU0008 Meta-analysis of the association of smoking and PTPN22 R620W genotype on autoantibody status and radiological erosions in rheumatoid arthritis. (23rd January 2014) - Taylor, L.H.; Twigg, S.; Worthington, J.J.; Emery, P.; Morgan, A.W.; Wilson, A.G.; Teare, M.D.
Abstract : Background: Smoking has been linked to production of anti-citrullinated protein antibodies (ACPA) in HLA-DRB1 shared epitope positive patients which has also been associated with a worse severity of rheumatoid arthritis (RA) [1, 2]. In addition, a single amino acid change R620W (rs2476601) in the protein tyrosine phosphatase non-receptor 22 (PTPN22) has been found to interact with smoking and ACPA positivity [3]. Despite this, a recent study [4] (N=532) found no evidence that smoking increased the risk of being ACPA positive. In addition, they reported a protective effect of smoking on the development of bone erosions in subjects who had ever smoked (OR=0.44, 95%CI 0.3-0.7, P≤0.0001) and a larger protective effect when subjects ever smoked in combination with carrying at least one of the PTPN22 single amino acid changes R620W (rs2476601) (OR=0.25, 95%CI 0.1-0.6, P=0.002) [4]. Objectives: To investigate the inter-relationships between smoking, protein tyrosine phosphatase non-receptor 22 (PTPN22) R620W genotype and anti-citrullinated peptide antibodies (ACPA) status and to investigate the inter-relationships between smoking, PTPN22 R620W genotype and presence of bone erosions in patients with RA. Methods: Six studies totalling 2680 RA patients were included in a Mantel-Haenszel fixed effects meta-analysis investigating ACPA status and eight studies totalling 3172 RA patients were included in a Mantel-Haenszel fixed effects meta-analysis investigating presence of erosive damage. Results: Evidence was found for an increase in the odds of ACPA positivity for ever smoking (OR=1.56, 95%CI 1.28-1.90, p=8.5 ×10 -6 ), carriage of at least one of the PTPN22 risk alleles (OR=1.50, 95%CI 1.13-2.00, P=0.0055) and both ever smoking and carriage of at least one of the PTPN22 risk alleles (OR=2.22, 95%CI 1.69-2.91, P=8.3×10 -9 ). There was no evidence of an association between presence of erosive damage and smoking status or carriage of PTPN22 risk alleles. Conclusions: This meta-analysis indicates that both smoking and having the PTPN22 risk allele affect the risk of ACPA positivity, however, neither PTPN22 nor smoking is associated with erosive damage. References: Baka Z, Buzas E, Nagy G. Rheumatoid arthritis and smoking: putting the pieces together. Arthritis Research & Therapy. 2009; 11(4). Lee DM, Phillips R, Hagan EM, Chibnik LB, Costenbader KH, Schur PH. Quantifying anti-cyclic citrullinated peptide titres: clinical utility and association with tobacco exposure in patients with rheumatoid arthritis. Annals of the Rheumatic Diseases. 2009; 68(2):201-208. Morgan AW, Thomson W, Martin SG, Carter AM, Erlich HA, Barton A, et al. Reevaluation of the Interaction Between HLA-DRB1 Shared Epitope Alleles, PTPN22, and Smoking in Determining Susceptibility to Autoantibody-Positive and Autoantibody-Negative Rheumatoid Arthritis in a Large UK Caucasian Population. Arthritis and Rheumatism. 2009; 60(9):2565-2576. Salliot C, Dawidowicz K, Lukas C, Guedj M, Paccard C, Benessiano J, et al. PTPN22 R620W genotype-phenotype correlation analysis and gene-environment interaction study in early rheumatoid arthritis: results from the ESPOIR cohort. Rheumatology. 2011; 50(10):1802-1808. Disclosure of Interest: None Declared